Survey results of the STOPSTORM consortium about stereotactic arrhythmia radioablation in Europe. (19th May 2022) - Grehn, M; Mandija, S; Andratschke, N; Zeppenfeld, K; Blamek, S; Fast, M; Botrugno, C; Blanck, O; Verhoeff, J; Pruvot, E
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Horizon 2020 research and innovation programme Background/Introduction: In patients with structural heart disease (SHD), ventricular tachycardia (VT) plays a decisive role in sudden cardiac death. VT patients are often treated with antiarrhythmic medication and catheter ablation. For refractory VTs, STereotactic Arrhythmia Radioablation (STAR) delivered to the underlying VT substrate has recently been introduced and showed promising results for otherwise untreatable patients. [1] Purpose: The purpose of the STOPSTORM consortium is to harmonize and optimize STAR across Europe. It consists of 31 members including 24 electrophysiology and 22 radiation oncology departments performing or participating in STAR throughout eight European countries. To obtain initial overview of organization, equipment, procedures, experiences, and quality levels for STAR, a detailed survey was circulated among STOPSTORM members. Methods: The survey included questions for electrophysiology (18 questions), radiation oncology (24 questions) and medical physics (23 questions). The survey was the first step for accreditation of the centres and therefore mandatory for all consortium members. Results: All centres participating in STOPSTORM completed the survey. 16 centres performed a total of 84 STAR treatments until May 2021 and 11 centres already participate in clinical trials for STAR. Annual number of VT ablations in SHD: less than 20 (17%), 20-50 (50%), 50-100 (21%), more than 100 (12%) and epicardial: less than 20 (71%), 20-50 (17%), n/s (12%). An overview of the availability of a clinical program for catheter ablation of ventricular arrhythmia with certification of the respective national cardiology society and the practice of general quality audits for ablation is given in figure 1. Participation in multicentre clinical trials in cardiology/EP were indicated by 19 departments (79%). Target volume definition is based on invasive electroanatomical mapping during VT (96%), pace mapping (75%), reduced voltage areas (63%) and/or late ventricular potentials (75%). Half of the centres includes the clinical VT substrate, while the other half includes the whole arrhythmogenic substrate. Non-invasive surface ECG mapping has so far found little application: used clinically (13%), research purposes (8%) and evaluation (4%). Stereotactic Body Radiotherapy experience (> 10 years: 82%, > 200 p.a.: 59%) is high. In all but one clinic, a dose of 25 Gy in a single fraction is applied. The prescription method, planning technique and inhomogeneity in the target volume, however, varies greatly. All departments perform patient-specific plan verifications for STAR, but with various evaluation criteria. Conclusion: Experience in STAR within the STOPSTORM consortium is adequate, while the survey shows areas of harmonization and optimization need for substrate mapping, target delineation, dosimetry and quality assurance which will be addressed in the STOPSTORM project work-packages.